Angiotensin‐converting enzyme and apolipoproteins genes polymorphism in coronary artery disease - Mansur, Antonio P. (Clin Cardiol, 2009)
Background: Association between angiotensin‐converting enzyme (ACE) as well as apolipoprotein (apo) AI, B, and E polymorphisms and dyslipidemia and coronary artery disease (CAD) is controversial. Hypothesis: This study assessed the distribution of ACE insertion/deletion, apo AI A/G mutation, apo B signal peptide insertion/deletion, apo B XbaI restriction fragment length, and apo E polymorphisms in 388 nondiabetic patients. Methods: The study population included 112 patients with stable CAD, 139 patients with acute myocardial infarction (AMI), and 137 age‐matched control subjects. Results: Univariate analysis showed higher prevalence of XbaI X+/X+ genotype in patients with CAD (p = 0.02). Angiotensin‐converting enzyme and apo polymorphisms were not associated with lipid levels or severity of CAD. When all genotypes known to be related to CAD, such as ACE DD, apo AI GG, apo B del/del, and XbaI X+X+, and E4 allele of apo E, were pooled, again no significant differences among groups were seen. Multivariate regression analysis disclosed traditional risk factors and elevated levels of apo B for men and reduced levels of apo AI for women as independent variables for CAD. Conclusions: In addition to traditional coronary risk factors, apo B and AI could be considered predictors of CAD. No association between either form of CAD and polymorphisms was noted.